Sludge and slime : oil spills in our world - Greeley, August (New York : PowerKids Press, 2003)
Explores what oil is and how it is used, the harm that is done when it is spilled into the ocean, and what can be done in the future to prevent such disasters as the 1989 wreck of the Exxon Valdez.
Includes bibliographical references (p. 23) and index.
4.1.
4.1
3-6
Keywords: Oil spills -- Environmental aspects -- Juvenile literature; Oil spills -- Environmental aspects; Oil spills -- Environmental aspects